Estudo comparativo entre o modal rodoviário e a cabotagem no Brasil para a soja - Souza, Jaiana Gomes dos Santos (Universidade Federal de São Carlos, 2020)
With the new market requirements and the needs of the country, the demand for a more economical and adequate transport system has induced the improvement of the waterway system, especially cabotage. This work has as general objective to compare the modalities of road transport and cabotage for soybeans, in varieties such as accessibility, routes and quantity to be transported while the specific ones are: to raise the exported quantities of soybeans together with their regions of origin of the product, to identify the main transport modal and ports of destination of the product, to indicate where the cabotage terminals are located and which are used for soybean flow , assess the potential locations where intermodality can be implemented, using road transport and the cabotage system. The work was conducted by the use of secondary data obtained through bibliographic reviews, books, academic papers, sites of public and private institutions, among other productions existing in the literature related to the area of study. The analysis was descriptive and quantitativebased on the theoretical field in an extensive and exploratory way. The main results are: the identification of the leadership of the state of Mato Grosso, in the last 5 years, as the largest Brazilian soybean producer, being also the largest Brazilian state that exports soybeans - reaching about US$ 7 billion FOB - followed by Rio Grande do Sul, Paraná, Goiás and São Paulo; with regard to the main buyers of soybean grain produced in Brazil, the main destinations were: China, Europe and Iran; the Port of Santarém (PA) can be considered an alternative for the export of soybeans from Mato Grosso and, the main public ports in the flow of soybeans, to the foreign market, by the North Exit, were those of Santarém, pará, and Itaqui, in Maranhão It is concluded that the investment and the access to intermodality with the use of cabotage is possible to drain , not only soybeans, but grains such as corn, due to the economic advantage and reduction of environmental impacts and for transporting large amounts.
Comparative study between road modal and cabotage in Brazil for soybeans
Keywords: Transporte aquaviário; Portos; Escoamento; Rodovias; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS